Fesibility study of renewable energy-based microgrid hybrid system in Berbera Somaliland - Osman, Mustafe Adam (2018)
Somaliland is a country that has not recognised internationally since it gets its independence in 1991, which has been suffering from electricity crisis due to high losses of electricity, less trained personnel, shortage of efficient technical plan, poor infrastructure and high cost of energy (COE) comparing to neighbour countries. The purpose of this project is to come up with plan to reduce this high COE by making economic feasibility to both the existing system of diesel system and proposing renewable energy-based microgrid system in Berbera Power Generation Company. Hybrid Optimization Model of Renewable Energy (HOMER) simulation software is applied to implement cost benefit analysis for both the existing and proposed model. The existing system is evaluated and studded how many litters of diesel the generators uses annually, the cost of energy and the amount of carbon emission that the system produces yearly. Renewable based hybrid microgrid system that consist of two renewable energy resources (wind and PV), two diesel generators, battery storage and converter is optimized in this project. Hence, the proposed system with renewable fraction of 55% can reduce the cost of energy 29% and provides less carbon emission of 40% then the existing system of diesel based system. Last but not least, this project recommended hybrid microgrid system that has less cost of energy ofUSD 0.262/kWh and environmental friendly system in Berbera Somaliland.